The Implementation of Quizizz to Enhance the Grammatical Ability of the Eleventh Graders - Nurhalyza, Anita Lucy (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This paper aims to improve grammar, especially in writing. Questions based on technological media will further explore the potential for writing practice. The participants in this paper were Class XI students at Hang Tuah 2 Sidoarjo High School. This learning was developed with the help of the Quizizz interactive quiz application. The students were exposed to online learning using Quizizz to improve their writing skills. The findings of this study confirmed that the students who were taught to write using proper and appropriate grammar achieved better grades than before. This type of research is quantitative experimental research. This research has three tests, namely descriptive test, normality test, and Whitney test. These stages determine the mean, median, and mode values. This development research uses quantitative descriptive methods. The descriptive research results showed that the highest score was 75, and the smallest was 12.5. For the normality test, data is not normally distributed. Based on the results of the Mann-Whitney test, Grammar assisted by the Quizizz application is declared valid or feasible to use in teaching and learning activities.